2012
DOI: 10.1164/rccm.201201-0117oc
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin CD151 Protects against Pulmonary Fibrosis by Maintaining Epithelial Integrity

Abstract: Rationale: Idiopathic pulmonary fibrosis (IPF) is a chronic pulmonary disorder of unknown etiology with few treatment options. Although tetraspanins are involved in various diseases, their roles in fibrosis have not been determined. Objectives: To investigate the role of tetraspanin CD151 in pulmonary fibrosis. Methods: CD151 knockout (KO) mice were studied by histological, biochemical, and physiological analyses and compared with wildtype mice and CD9 KO mice. Further mechanistic analyses were performed in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 55 publications
1
35
1
Order By: Relevance
“…41 Consistent with this notion was a marked increase in the active form of SMAD2, as well as expression of total SMAD4, upon CD151 removal (Fig. 6A).…”
Section: Cd151 Removal Coincides With the Induction Of Transcription supporting
confidence: 74%
See 1 more Smart Citation
“…41 Consistent with this notion was a marked increase in the active form of SMAD2, as well as expression of total SMAD4, upon CD151 removal (Fig. 6A).…”
Section: Cd151 Removal Coincides With the Induction Of Transcription supporting
confidence: 74%
“…This observation is consistent with a recent study on the in vivo effect of CD151 removal in another epithelial tissue. 41 Our unpublished data, however, do suggest that altered TGFb-mediated signaling in mammary tissues may not stem from a direct effect of CD151. Rather, it may result from CD151-mediated activation of Slug.…”
Section: Cd151 Mediates Normal Development Of Mammary Glands By Reprementioning
confidence: 67%
“…This model is supported by studies demonstrating that pulmonary fibrosis can occur following the ablation of factors that normally maintain epithelial integrity without any preceding inflammation (25,39,45). The model suggests that chronic injury results in the activation of a subset of bronchial and AEC that become hyperplastic with enlarged cell shape, whereas another subset of alveolar type II cells that are sensitive to chronic injuries undergo cell-flattening events.…”
Section: Discussionmentioning
confidence: 83%
“…A current model of IPF suggests that compromised epithelial integrity is a major component of pathogenesis and may in fact initiate the fibrotic response (16,20,29,34,39). This model is supported by studies demonstrating that pulmonary fibrosis can occur following the ablation of factors that normally maintain epithelial integrity without any preceding inflammation (25,39,45).…”
Section: Discussionmentioning
confidence: 88%
“…Molecular studies involving CD151 with cancer progression and metastasis to date have focused on in vitro and grafting models. These studies have shown that knockdown/-out or mutation of CD151 decreases cell motility (16)(17)(18)(19)(20)(21)(22) and/or decreases experimental metastasis (23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%